Ligand effects in a heteroleptic bis-tridentate iron(iii) spin crossover complex showing a very high T1/2 value. Issue 7 (9th December 2015) - Phonsri, Wasinee; Martinez, Victor; Davies, Casey G.; Jameson, Guy N. L.; Moubaraki, Boujemaa; Murray, Keith S.
Abstract : The iron(iii ) bis-tridentate complex [Fe(3-OMe-SalEen)(thsa)] is the first heteroleptic iron(iii ) spin crossover complex and displays a very high T 1/2 value and weak thermal hysteresis. Intermolecular structural details are related to the cooperativity features. Abstract : We describe the first example of a bis-tridentate heteroleptic iron(iii ) spin crossover (SCO) complex, [Fe(3-OMe-SalEen)(thsa)]. Compared to the parent homoleptic compounds, the spin crossover features in the heteroleptic species are enhanced with a gradual–abrupt spin transition at 344 K. Clear correlations between π–π interactions and the T 1/2 value have been revealed.